(untitled) (Global Journal of Science Frontier Research, 2016)
In an attempt to find an origin of dark energy it is found that the hypothetical pair of gravitationally bound Planckeon of mass m pl 0.5g and the Higgs boson of masss m H !0 -4 m pl creates a negative attractive potential -Gm pl m H /l pl . The corresponding temperature of thermal creation T 10 28 K is higher than T 10 27 K accepted by the standard inflationay cosmology, but within the asymptotic limit T ∞ interpolated from Hubble’s expansion history to the point origin of the Hubble universe.